Kedudukan Anak Dalam Pewarisan Menurut Hukum Waris Adat(Study Kasus di Desa Slendro Kecamatan Gesi Kabupaten Sragen) - Anggarini, Sylvianan; , Septarina Budiwati, S.H., M.H (2016)
This research aims to know the Division of inheritance according to customary law, as well as the position of the child in the Division of inheritance according to customary law. The method of the approach used in this study is the empirical approach method, this type of research is both descriptive because this research aims to provide an overview of the State of the subject and object of research or as is. Using primary data and secondary data. Method of data collection in this research study by means of interviews and the study of librarianship. The analysis used in the study authors is a normative method of qualitative data analysis. Based on the results of the research and the discussion then it can be inferred that the existence and the position of the child in the customary law of inheritance can be classified into four parts, namely, children, adopted children, stepchildren and foster children. The whereabouts of the children entitled to inherit his parents ' heritage treasures. The existence of the adopted child has the right to inherit the property along with his adoptive parents as well as the right to inherit the property of his biological parents. The position of the stepchildren are eligible to inherit the possessions legacies of his parents and has no right to inherit the property of origin of his parents. While the position of foster care are not entitled to get the treasure relics of foster parents, but still has the right to inherit property from his parents.